HUBUNGAN PENGETAHUAN DAN GAYA HIDUP DENGAN UPAYA PENCEGAHAN STROKE PADA PEDERITA HIPERTENSI DEWASA DI WILAYAH KERJA PUSKESMAS AMBACANG PADANG TAHUN 2025 - Khairul Andri; Noly Papertu Englardi; Fitriani Fitriani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Stroke is the third leading cause of death after coronary heart disease and cancer, with the number of stroke cases in West Sumatra reaching 2,345 per 100,000 population (Ministry of Health of the Republic of Indonesia, 2025). Many hypertension sufferers neglect stroke prevention efforts due to inadequate knowledge and unhealthy lifestyles. The purpose of this study was to determine the relationship between knowledge and lifestyle and stroke prevention efforts among adult hypertensive patients in the Ambacang Community Health Center (Puskesmas) working area in 2025.This study was quantitative with a cross-sectional study design. Questionnaires were distributed from March 3 to 8, 2025, to a sample of 73 hypertensive adults. The sampling technique used was the proportion estimation formula. Data analysis is presented in the form of a frequency table using the Chi-square test using SPSS.The study revealed that 50.7% of respondents had good knowledge, 63.0% had a good lifestyle, and 47.9% of respondents had poor stroke prevention efforts. Bivariate analysis showed a correlation between knowledge and stroke prevention efforts in hypertensive adults (p-value = 0.023), and a significant correlation between lifestyle and stroke prevention efforts in hypertensive adults (p-value = 0.000).It is hoped that healthcare workers can use this information as a reference in providing health services, such as providing more comprehensive and accurate information about hypertension and stroke, which will ultimately improve the efforts of hypertensive patients to prevent stroke.Keywords: Stroke, Knowledge, Lifestyle